Proceedings of the 5th Information Interaction in Context Symposium 2014
DOI: 10.1145/2637002.2637022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive abilities on information search for tasks of varying levels of complexity

Abstract: Although web search engines are designed as one-size-fits-all tools, people do not come in one size, but instead vary across many different attributes. One such attribute is cognitive ability. Because information search is primarily a cognitive activity, understanding the extent to which variations in cognitive abilities impact search behaviors and outcomes is especially important. We describe a study in which we explore how people's cognitive abilities affect their search behaviors and perceptions of workload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 56 publications
6
40
3
Order By: Relevance
“…Although they performed significantly better on the cause–effect task compared to the controversial topic task, time on task and time to formulate an answer did not differ significantly between those two tasks but was longer for both tasks when compared to the fact‐finding task. With regard to time on task, these findings are in line with earlier research, which also showed that more complex tasks required more time (Borlund & Dreier, ; Brennan et al, ; Liu et al, ). Participants needed more time to formulate an answer for the cause–effect task and the controversial topic task, which might indicate they experienced difficulty in those two tasks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although they performed significantly better on the cause–effect task compared to the controversial topic task, time on task and time to formulate an answer did not differ significantly between those two tasks but was longer for both tasks when compared to the fact‐finding task. With regard to time on task, these findings are in line with earlier research, which also showed that more complex tasks required more time (Borlund & Dreier, ; Brennan et al, ; Liu et al, ). Participants needed more time to formulate an answer for the cause–effect task and the controversial topic task, which might indicate they experienced difficulty in those two tasks.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the findings of other studies (Liu et al, ; Singer et al, ). Furthermore, several studies showed that more complex tasks require more time on task (Borlund & Dreier, ; Brennan, Kelly, & Arguello, ; Liu et al, ; Kelly et al, ) as well as for more specific time‐based measures like search time, time on SERPs, and reading time (Singer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Various types of cognitive abilities have been studies regarding how they influence online information search. High PS users also reported lower levels of workload (Brennan, Kelly, & Arguello, 2014). It has been found that high PS users located relevant materials more effectively, that is, showing higher precision and recall (Allen, 1992); and more efficiently, that is, using less time (Al-Maskari & Sanderson, 2011).…”
Section: Rlc Relationship Between Contextual Factors and Search Behamentioning
confidence: 96%
“…Tasks: Our commercial partner supplied a number of typical work tasks performed by their analysts. Using a similar approach to Brennan et al [21], we selected ten work tasks, five of which we considered simple, and five of which we considered complex. The difficulty of these tasks was determined during a pilot study and measured by the number of interactions required to complete the task (i.e.…”
Section: Experimental Set-upmentioning
confidence: 99%